Pedagogical Conditions for the Formation of Moral Education of Elementary Schoolchildren by Means of Didactic Literature Works - Belgibayeva, Gulnur A.; Kulanova, Sandugash Sh.; Kerimbekova, Akbope A.; Aitenova, Dinara O.; Belgibayev, Mukhtar A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of this study is to identify the pedagogical conditions for the formation of the moral education of elementary school children with psychological characteristics using didactic works. Background: Parenting and education are integral parts of the development of society. In this connection, moral education in elementary school is a prospect for the development of Kazakhstani society as a whole. Method: The main research methods were content analysis, generalisation and concretisation, theoretical analysis of scientific, pedagogical and methodical literature, pedagogical experience. Results: In the course of the study, the organisational forms of the educational process, the selection of didactic works in the discipline "Literary reading" of grade 4 were analysed and generalised. The pedagogical conditions for the formation of the moral education of elementary school students (general, private and specific), as well as the methods of moral education (verbal, practical and visual), are determined. The types of didactic works (stories, legends, poems, proverbs and instructive words) were analysed, and characters that educate morality were identified. Conclusion: It was found that the specifics of the pedagogical conditions for the formation of the moral education of elementary school students with individual mental characteristics lie in the specifics of the discipline itself, the content of didactic works, tools and the results of the teacher’s work with schoolchildren, which is reflected in the level of morality of schoolchildren, that is, on the object of formation.